A gel polymer electrolyte, a secondary battery including the same, and an electric device
Patent Information
- Application Number
- CN202610961377.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-20
AI Technical Summary
[0002]传统液态电解液虽具有高离子电导率(10-3-10-2mS/cm),但存在泄漏、易燃等安全隐患;固态聚合物电解质(如PEO基)安全性高,但室温离子电导率低(<0.1 mS/cm)
本申请提供的凝胶聚合物电解质通过引入包括单元A和单元B的聚合物,其中单元A包括砜基、氰基中的至少一种,单元B包括酰胺基、氟代烷基中的至少一种;后续应用于二次电池时,得到的二次电池具有良好的循环性能和倍率性能。
Smart Images

Figure SMS_25 
Figure SMS_26 
Figure SMS_27
Abstract
Description
Technical Field
[0001] This application relates to the field of battery energy storage technology, and in particular to a gel polymer electrolyte, a secondary battery containing the same, and an electrical device. Background Technology
[0002] Traditional liquid electrolytes have high ionic conductivity (10). -3 -10 -2 While polymer electrolytes (such as PEO-based electrolytes) offer high safety, they also have low room-temperature ionic conductivity (<0.1 mS / cm), posing safety hazards such as leakage and flammability. Solid polymer electrolytes (such as PEO-based electrolytes) offer high safety, but their room-temperature ionic conductivity is low (<0.1 mS / cm). Existing gel electrolytes (30%-70% electrolyte content) fix the electrolyte through a polymer network, but their kinetic performance deteriorates significantly, failing to meet the fast charging requirements above 3C. The fundamental reason is that the polymer backbone competes with solvent molecules for lithium ions, leading to an increased lithium-ion migration activation energy. Simultaneously, the inherently weak antioxidant capacity of polymers prevents them from meeting the positive electrode potential exceeding 4.5V required for consumer batteries. Summary of the Invention
[0003] The purpose of this application is to solve the above-mentioned technical problems and to propose a gel polymer electrolyte, which, when applied to a secondary battery, results in a secondary battery with excellent high cycle capacity retention, low cycle thickness expansion rate, and high 3C discharge capacity ratio, a secondary battery containing the electrolyte, and an electrical device thereof.
[0004] To achieve the above objectives, a first aspect of this application provides a gel polymer electrolyte comprising a polymer and an electrolyte, wherein the polymer comprises unit A and unit B; Unit A includes at least one of sulfone and cyano groups; Unit B includes at least one of amide group and fluoroalkyl group.
[0005] As an embodiment of this application, the polymer in the gel polymer electrolyte has a mass percentage greater than 0% and less than or equal to 3%.
[0006] As an embodiment of this application, unit A includes at least one of the structures shown in formulas a-d: Formula a Formula b Formula c Formula d; Among them, R1 is selected from C1-C 20 Alkyl, C1-C 20 Oxyalkylene, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20Any one of the fluoroaromatic groups; R2 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R10 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R11 and R12 are selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups.
[0007] As an embodiment of this application, unit B includes at least one of the structures shown in formulas e-h: Formula e Formula f Formula g, Formula h; Among them, R3 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R4 and R5 are each independently selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R6 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R7 and R8 are each independently selected from hydrogen, C1-C. 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any of the fluoroaromatic groups, and at least one of R6, R7, and R8 includes C1-C. 20 Fluorinated alkyl or C6-C 20 Fluorinated aromatic groups; R9 is selected from C1-C 20 Fluoroalkyl, C6-C 20 Any one of the fluoroaromatic groups.
[0008] As an embodiment described in this application, unit A has the structure shown in formula a, and R1 is selected from ethyl.
[0009] As an embodiment described in this application, unit A has the structure shown in formula c, and R10 is selected from ethyl.
[0010] As an embodiment described in this application, unit B has the structure shown in formula e, and R3 is selected from methylene.
[0011] As an embodiment described in this application, unit B has the structure shown in formula h, and R9 is trifluoromethyl.
[0012] As an embodiment described in this application, the polymer contains 10-40% molar percentage of unit A.
[0013] As an embodiment of this application, the electrolyte includes an organic solvent and a lithium salt; The organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, methyl ethyl carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,3-dioxolane, dimethoxyethane, tetraethylene glycol dimethyl ether, ethyl acetate, and ethyl propionate. The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium di(trifluoromethanesulfonyl)imide, lithium bis(oxalato)borate, lithium difluorooxalato)borate, and lithium hexafluoroarsenate.
[0014] In a second aspect, this application provides a secondary battery comprising the gel polymer electrolyte described in this application.
[0015] In a third aspect, this application provides an electrical device comprising the secondary battery described in this application.
[0016] Compared with the prior art, the beneficial effects of this application are: The gel polymer electrolyte provided in this application introduces a polymer comprising unit A and unit B, wherein unit A comprises at least one of sulfone group and cyano group, and unit B comprises at least one of amide group and fluoroalkyl group; when subsequently applied to a secondary battery, the resulting secondary battery exhibits good cycle performance and rate performance. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0018] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0019] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0020] Unless otherwise specified, all reagents or instruments used in this application are commercially available products.
[0021] In one embodiment of this application, a first aspect of this application is provided, which provides a gel polymer electrolyte comprising a polymer and an electrolyte, wherein the polymer comprises unit A and unit B; Unit A includes at least one of sulfone and cyano groups; Unit B includes at least one of amide group and fluoroalkyl group.
[0022] This application research found that the gel polymer electrolyte provided in this application, by introducing a polymer including unit A and unit B, wherein unit A includes at least one of sulfone group and cyano group, and unit B includes at least one of amide group and fluoroalkyl group, when subsequently applied to a secondary battery, results in a secondary battery with good cycle performance and rate performance.
[0023] Specifically, unit A includes at least one of sulfone and cyano groups. Sulfone and cyano groups are strong electron-withdrawing groups, and their presence in the polymer can effectively reduce the overall HOMO value of the polymer, thereby improving the high-voltage stability of the polymer. Furthermore, if the positive electrode active material of the secondary battery includes cobalt ions, the sulfone and cyano groups can also provide coordination electrons to the high-valence cobalt ions suspended on the positive electrode surface, stabilizing the positive electrode structure, preventing cobalt from migrating to the lithium layer in the positive electrode, and further improving the cycle stability of the corresponding secondary battery.
[0024] Unit B includes at least one of amide group and fluoroalkyl group. The amide group and fluoroalkyl group have sites that can easily form hydrogen bond donors, and can combine with more anions and solvent molecules, thereby reducing the radius of solvated lithium ions, increasing the migration speed of solvated lithium ions, and improving the overall ionic conductivity of the gel polymer electrolyte; thus effectively improving the rate performance of the corresponding secondary battery.
[0025] The polymer contains both unit A and unit B, and the groups in unit A and unit B have a synergistic effect. For example, the amide group and / or fluoroalkyl group in unit B have a weaker coordination ability for lithium ions and are more capable of adsorbing anions and dissociating lithium salts; while the sulfone group and / or cyano group in unit A have a stronger lithium ion binding ability. The polymer formed by the two can form an alternating strong and weak coordination environment, forming a dynamic shell structure near the polymer backbone, which further enhances the lithium ion transport ability, thereby improving the fast charging capability and high voltage resistance of the corresponding secondary battery (able to meet the cutoff voltage above 4.5V). This is reflected in the high capacity retention rate, low thickness expansion rate, and high 3C discharge capacity ratio of the resulting secondary battery before and after cycling.
[0026] It should be noted that the testing methods for the groups in unit A and unit B of the polymer are as follows: 1) Fully discharge the battery to be disassembled to 2.8V under load in an argon-filled glove box (water and oxygen content below 0.1 ppm). Remove the positive electrode, negative electrode, and separator separately. In the glove box, gently scrape off the gel microparticle coating on the separator surface with a ceramic blade and collect the powder. Cut the electrode into small fragments and powder, and place them in centrifuge tubes. Add sufficient washing solvent (such as dimethyl carbonate (DMC) or ethyl acetate) to the centrifuge tube containing the sample, and shake or sonicate thoroughly for 5-10 min to separate the gel microparticles from the electrode substrate or residual electrolyte. Repeat the washing 2-3 times. Centrifuge the washed suspension at 8000-10000 rpm for 10-15 min. After centrifugation, the gel microparticles and electrode active material settle to the bottom. Decant the supernatant to remove dissolved lithium salts and organic solvents. Transfer the centrifuged precipitate to a vacuum oven and vacuum dry at 60-80°C for 12-24 h to obtain a dry powder containing gel microparticles. If the active material on the electrode interferes with subsequent tests, it can be further purified by sieving or density gradient centrifugation.
[0027] 2) Infrared Spectroscopy: The dried gel microparticle powder was mixed with KBr at a mass ratio of 1:100, and then ground thoroughly in an agate mortar. After being molded, the mixture was vacuum-pressed to 10 MPa and pressed into a transparent thin film for infrared detection. The peaks were: sulfone group (-SO2-): ~1315 cm⁻¹ and ~1100 cm⁻¹; cyano group (-CN): sharp peak at ~2230 cm⁻¹; amide group (-CONH-): ~3300 cm⁻¹ (NH stretching), ~1640–1680 cm⁻¹ (amide I band), ~1540 cm⁻¹ (amide II band). 3) X-ray photoelectron spectroscopy: Sprinkle the dried gel microparticle powder evenly onto double-sided conductive tape, gently blow away any loose powder with a bulb syringe or use a special tablet press to firmly press the powder onto the indium foil; the sample size should not exceed 1 cm × 1 cm, and test it as soon as possible after removing it from the glove box. Analyze the following characteristics: C 1s (C≡N, ~286.3 eV), N 1s (amide group, ~399.8 eV), F 1s (CF bond), S 2p (sulfone group, ~168 eV). 4) Thermal pyrolysis-gas chromatography-mass spectrometry: A small amount of dried gel microparticle powder is pyrolyzed at high temperature, and the fragment products are introduced into GC / MS to identify whether they contain characteristic fragments such as methacrylonitrile, N,N-dimethylacrylamide, and phenyl vinyl sulfone.
[0028] 5) Combine infrared and X-ray photoelectron spectroscopy with thermal pyrolysis-gas chromatography-mass spectrometry to analyze the types of functional groups in the polymer.
[0029] In one embodiment, the polymer has a mass percentage in the gel polymer electrolyte that is greater than 0% and less than or equal to 3%.
[0030] For example, the mass percentage of the polymer in the gel polymer electrolyte can be any point value or any two points between 0% and 3%, such as 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, etc.
[0031] In one embodiment, the polymer comprises a mass percentage of 0.25% and less than or equal to 2% in the gel polymer electrolyte.
[0032] In one embodiment, the polymer comprises a mass percentage of greater than or equal to 1% and less than or equal to 2% in the gel polymer electrolyte.
[0033] This application research found that the mass percentage of the specific polymer provided in the gel polymer electrolyte affects the ionic conductivity and also affects the high voltage resistance. When the mass percentage of the polymer in the gel polymer electrolyte is further selected within the above range, especially within the further preferred range, it can effectively ensure that the gel polymer electrolyte has high ionic conductivity and excellent high voltage resistance, thereby achieving good cycle performance and rate performance of the corresponding secondary battery.
[0034] It should be noted that the test method for the mass percentage of the polymer in the gel polymer electrolyte is as follows: Gel microparticle powder is obtained using a method similar to that used to analyze the types of functional groups in the polymer, followed by the following tests: (1) After the secondary battery to be tested is fully discharged, it is disassembled in a glove box filled with argon gas, and the membrane or electrode containing gel electrolyte is taken out and its mass is recorded as m gel. (2) The above sample was soaked in dimethyl carbonate (DMC) and subjected to Soxhlet extraction under reflux for 24-48 hours to remove lithium salts and organic solvents from the electrolyte. The insoluble matter after extraction was vacuum dried to constant weight and its mass was recorded as m_crude. (3) Take the dried crude polymer powder and use an organic elemental analyzer (EA) to determine the mass fraction of nitrogen and / or sulfur, and record it as w_actual; (4) Based on the molar ratio of monomer A and monomer B and their molecular structure, calculate the theoretical characteristic element content of the target polymer using the following formula: Among them, A E N is the atomic weight of the characteristic element. A N B These represent the number of atoms of the characteristic elements in units A and B, respectively, in MW. A MW B The molecular weights of the repeating units corresponding to units A and B are n, respectively. A n B These are the amounts of substance of units A and B, respectively. (5) Calculate the mass percentage of the target polymer in the gel polymer electrolyte using the following formula: It should be noted that when the ratio of the measured value of w to the theoretical value of w is in the range of 90% to 110%, it indicates that the purity of the target polymer in the crude polymer is high and the calculation results are accurate and reliable. When the ratio exceeds 110%, it indicates that there may be impurities containing characteristic elements in the crude polymer (such as residual nitrogen-containing lithium salts), and further purification is required before re-measurement.
[0035] Specifically, the w theory involves solid-state nuclear magnetic resonance (NMR) spectroscopy: the dried gel microparticle powder is subjected to NMR spectroscopy, and analyzed in conjunction with the above-mentioned thermal pyrolysis-gas chromatography-mass spectrometry (Py-GC / MS) to determine the specific chemical structure of unit A and unit B in the polymer and their copolymer molar ratio. Based on this, the theoretical molecular weight of the repeating unit of the copolymer and the theoretical nitrogen (or sulfur) content are calculated. The analysis was performed using an organic elemental analyzer (EA). Specifically, the sample was ground to a fineness of 150-200 mesh (approximately 75-100 micrometers) using an agate mortar. Grinding was thorough to ensure uniform powder mixing. An ultra-micro balance with an accuracy of 0.001 mg was used. For CHNS mode, 2-5 mg of sample was typically weighed. The sample was placed in a tin boat (tin bag), folded and sealed tightly with tweezers to remove air, and the test was initiated to determine the actual mass fraction of nitrogen and / or sulfur in the polymer powder.
[0036] In one embodiment, the unit A includes at least one of the structures shown in formulas a-d: Formula a Formula b Formula c Formula d; Among them, R1 is selected from C1-C 20 Alkyl, C1-C 20 Oxyalkylene, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R2 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R10 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R11 and R12 are selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups.
[0037] This study found that further selecting the structure of unit A as described above can more effectively reduce the overall HOMO value of the polymer, improve the high-voltage stability of the polymer, and better stabilize the cathode structure, thereby achieving superior overall performance of the secondary battery.
[0038] In one embodiment, the unit B includes at least one of the structures shown in formulas e-h: Formula e Formula f Formula g, Formula h; Among them, R3 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R4 and R5 are each independently selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R6 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R7 and R8 are each independently selected from hydrogen, C1-C. 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any of the fluoroaromatic groups, and at least one of R6, R7, and R8 includes C1-C. 20 Fluorinated alkyl or C6-C 20 Fluorinated aromatic groups; R9 is selected from C1-C 20 Fluoroalkyl, C6-C 20 Any one of the fluoroaromatic groups.
[0039] This study found that by further selecting the structure of unit B as described above, the radius of solvated lithium ions can be reduced more effectively, the migration speed of solvated lithium ions can be increased, thereby improving the overall ionic conductivity and achieving better comprehensive performance of the secondary battery.
[0040] In one embodiment, unit A has the structure shown in formula a, and R1 is selected from ethyl.
[0041] This application study found that the sulfone group (-SO2-) included in unit A is a strong electron-withdrawing group, which can effectively reduce the HOMO energy level of the polymer and significantly improve the high voltage resistance (up to >5.9V window); at the same time, if R1 is ethyl, the ethyl can act as a flexible side group to alleviate the segment rigidity caused by the sulfone group.
[0042] In one embodiment, unit A has the structure shown in formula c, and R10 is selected from ethyl.
[0043] This study found that the cyano group (-CN) in unit A can further lower the HOMO energy level and can react with high-valence transition metal ions (such as Ni) on the cathode surface. 4+ Co 3+ Coordination inhibits cation mixing and metal dissolution, stabilizing the cathode structure; if R10 is ethyl, it can further adjust the electron-withdrawing strength of the cyano group, while using steric hindrance to increase the free volume between chains, avoiding excessive reduction of ionic conductivity.
[0044] In one embodiment, unit B has the structure shown in formula e, and R3 is selected from methylene.
[0045] This application research found that unit B includes an amide group (-CONH-), and the NH group in the amide group acts as a hydrogen bond donor, which can efficiently capture anions (such as PF6). - This promotes lithium salt dissociation and reduces the radius of solvated lithium ions, thereby increasing the lithium ion transference number (up to 0.7). R3 is chosen as methylene, which can moderately adjust the hydrogen bond strength and prevent anions from being excessively bound, thus affecting conduction.
[0046] In one embodiment, unit B has the structure shown in formula h, and R9 is trifluoromethyl.
[0047] This study found that when unit B includes fluoroalkyl groups, especially trifluoromethyl (-CF3), it has the strongest electron-withdrawing effect and the highest fluorine content, which can broaden the electrochemical window and induce the formation of a stable interface layer rich in LiF on the electrode surface, suppressing side reactions; at the same time, it reduces the binding energy of the polymer backbone to lithium ions, which is conducive to the rapid migration of lithium ions.
[0048] This study found that when unit A and unit B are further selected to be of the above-mentioned types, the synergistic effect between the two is better, thereby achieving a higher post-cycle capacity retention rate and 3C discharge capacity ratio of the secondary battery, while achieving a lower post-cycle thickness expansion rate of the secondary battery.
[0049] In one embodiment, the polymer contains 10-40% molar percentage of unit A.
[0050] For example, in the polymer, the molar percentage of unit A can be any point value or any two-point range value between 10% and 40%, such as 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, etc.
[0051] In one embodiment, the polymer contains 20-30% molar percentage of unit A.
[0052] It should be noted that the molar percentage of unit A in the polymer is determined by elemental analysis, referring to the method for determining the mass percentage of the polymer in a gel polymer electrolyte. Then, nuclear magnetic resonance spectroscopy, combined with thermal pyrolysis-gas chromatography-mass spectrometry (Py-GC / MS), is used to determine the specific chemical structures of unit A and unit B in the polymer and their copolymerization molar ratio.
[0053] This study found that the molar percentage of unit A in the polymer affects the function of unit A and its interaction with unit B. When the mass percentage of unit A in the polymer is further selected within the above range, the overall performance of the secondary battery prepared subsequently is better.
[0054] In one embodiment, the electrolyte comprises an organic solvent and a lithium salt; The organic solvent is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), methyl ethyl carbonate (EMC), vinylene carbonate (VC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), ethyl butyl carbonate (EBC), dipropyl carbonate (DPC), 1,3-dioxolane (DOL), dimethoxyethane (DME), tetraethylene glycol dimethyl ether (TEGDME), ethyl acetate (EA), and ethyl propionate (EP). The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium di(trifluoromethanesulfonyl)imide, lithium bis(oxalato)borate, lithium difluorooxalato)borate, and lithium hexafluoroarsenate.
[0055] In one embodiment, the method for preparing the gel polymer electrolyte includes the following steps: S1. Add monomer A, which is used to form unit A, monomer B, which is used to form unit B, and initiator to the electrolyte to obtain a precursor solution; S2. Next, the precursor solution is injected into the battery and polymerized and cured in situ at 60-80°C for 4-16 hours to obtain a gel polymer electrolyte.
[0056] In some embodiments, the monomer A for forming unit A includes at least one of vinyl sulfone, methyl vinyl sulfone, ethyl vinyl sulfone, n-propyl vinyl sulfone, phenyl vinyl sulfone, benzyl vinyl sulfone, naphthyl vinyl sulfone, cyclohexyl vinyl sulfone, p-chlorophenyl vinyl sulfone, p-tolyl vinyl sulfone, p-nitrophenyl vinyl sulfone, allyl sulfone, allyl methyl sulfone, allyl phenyl sulfone, 4-vinylphenyl methyl sulfone, 4-vinylphenylphenyl sulfone, 4-isopropenylphenyl methyl sulfone, cyclic vinyl sulfone, acrylonitrile, methacrylonitrile, 4-vinylbenzyl nitrile, 2-cyanoacrylate acrylonitrile, 2-chloroacrylonitrile, 2-bromoacrylonitrile, 2-phenylacrylonitrile, methyl α-cyanoacrylate, α-cyanoacrylate, ethyl cyanoacrylate, and ethyl methacrylate.
[0057] In some embodiments, the monomer B used to form unit B includes at least one of trifluoroethyl acrylate, hexafluorobutyl methacrylate, dodecafluoroheptyl methacrylate, trifluoroethyl acrylate, trifluoromethylstyrene, acrylamide, methacrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N-isopropylacrylamide, N-hydroxymethylacrylamide, N-n-butylacrylamide, N-tert-butylacrylamide, N-allylformamide, N,N'-methylenebisacrylamide, N,N'-ethylethylenebisacrylamide, and diacetoneacrylamide.
[0058] In some embodiments, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, diisopropyl peroxide dicarbonate, lauroyl peroxide, and di-tert-butyl peroxide.
[0059] In some embodiments, the molar ratio of monomer A to monomer B is 1:(1.5-9).
[0060] In some embodiments, the molar percentage of the initiator is 0.001-2% based on the molar percentage of monomer A.
[0061] It is understandable that by controlling the types of monomers A and B, the structure of unit A and unit B in the polymer can be controlled.
[0062] It is understandable that by adjusting the amount of monomer A and monomer B added, the molar percentage of unit A in the polymer can be controlled.
[0063] It is understandable that by adjusting the amount of monomer A and monomer B added, the mass percentage of polymer in the gel polymer electrolyte can also be adjusted.
[0064] In a second aspect, this application provides a secondary battery comprising the gel polymer electrolyte described in this application.
[0065] In one embodiment, the secondary battery further includes a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer includes a positive active material, a positive conductive agent, and a positive binder.
[0066] This application does not have any special requirements for the positive electrode active material. For example, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium iron phosphate.
[0067] This application does not have any special requirements for the positive electrode binder. Exemplarily, the positive electrode binder includes at least one of polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.
[0068] This application does not have any special requirements for the positive electrode conductive agent. For example, the positive electrode conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0069] In some embodiments, the secondary battery further includes a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector, the negative active material layer including a negative active material, a negative binder and a negative conductive agent.
[0070] This application does not have any special requirements for the negative electrode active material. For example, the negative electrode active material includes at least one of graphite, silicon carbide, and silicon oxide.
[0071] This application does not have any special requirements for the negative electrode binder. Exemplarily, the negative electrode binder includes at least one of the following: polyacrylic acid, polymethacrylic acid, polyacrylate, polymethacrylate, polyacrylamide, styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylic acid-acrylonitrile-acrylamide copolymer, acrylic acid-acrylonitrile-acrylate copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acryloyl rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyvinyl alcohol, polyvinyl acetate, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, carboxymethyl chitosan, polyester, polyamide, polyether, polyimide, polycarboxylic acid ester, polycarboxylic acid, polyurethane, alginate, fluorinated polymer, chlorinated polymer, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropylene.
[0072] This application does not have any special requirements for the negative electrode conductive agent. For example, the negative electrode conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0073] In one embodiment, the secondary battery further includes a separator located between the positive electrode and the negative electrode.
[0074] The separator can be any type of separator suitable for batteries in the art. For example, the material of the separator includes, but is not limited to, at least one of polypropylene and polyethylene.
[0075] In a third aspect, this application provides an electrical device comprising the secondary battery described in this application.
[0076] In a third aspect, this application provides an electrical device comprising the secondary battery described in this application.
[0077] Example 1 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery includes the following steps: (1) Preparation of gel polymer electrolyte precursor solution Monomer A (methacrylonitrile, 0.1675 g, 0.0025 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 0.7425 g, 0.0075 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0164 g, 0.0001 mol) were added to 100 g of electrolyte, and then the mixture was heated and stirred at 65°C for 8 hours to obtain a precursor solution.
[0078] (2) Preparation of electrolyte In an argon-filled glove box, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7. Lithium hexafluorophosphate (LiPF6) was then added to the mixed solvent until the concentration reached 1.2 mol / L. After stirring until homogeneous, the electrolyte was obtained.
[0079] (3) Preparation of positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1. An appropriate amount of N-methylpyrrolidone (NMP) is added and stirred evenly. The mixture is then coated onto an aluminum foil current collector, dried, rolled, and cut to obtain the positive electrode sheet.
[0080] (4) Preparation of negative electrode sheet The negative electrode active material artificial graphite, conductive agent Super P, binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 8:1:0.5:0.5. An appropriate amount of deionized water is added and stirred evenly. The mixture is coated on a copper foil current collector and then dried, rolled, and cut to obtain the negative electrode sheet.
[0081] (5) Preparation of the separating membrane Polyethylene (PE) porous membrane is used as the separation membrane.
[0082] (6) Preparation of secondary batteries In an argon-filled glove box, the above-mentioned positive electrode, separator, and negative electrode are assembled in sequence into a CR2032 coin cell. The precursor solution obtained in step S1 is injected, and after sealing, the cell is placed in a 70°C oven and heated for 6 hours for in-situ polymerization and curing to obtain a secondary battery.
[0083] Examples 2-4 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that the preparation of the gel polymer electrolyte is carried out to achieve the change in the mass percentage of polymer in the gel polymer electrolyte as shown in Table 1. Specifically: Example 2: In step (1), monomer A (methacrylonitrile, 0.3350 g, 0.0050 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 1.4850 g, 0.0150 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0328 g, 0.0002 mol) were added to 100 g of electrolyte, and the rest of the operation was the same as in Example 1.
[0084] Example 3: In step (1), monomer A (methacrylonitrile, 0.5025 g, 0.0075 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 2.2275 g, 0.0225 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0492 g, 0.0003 mol) were added to 100 g of electrolyte, and the rest of the operation was the same as in Example 1.
[0085] Example 4: In step (1), monomer A (methacrylonitrile, 0.0419 g, 0.000625 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 0.1856 g, 0.001875 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0041 g, 0.000025 mol) were added to 100 g of electrolyte, and the rest of the operation was the same as in Example 1.
[0086] Examples 5-6 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that monomer A is changed to achieve a change in unit A. Specifically: Example 5: Replacing methylpropenyl sulfone with methyl vinyl sulfone; Example 6: 4-Vinylbenzylnitrile was used instead of methylpropenyl sulfone.
[0087] Examples 7-8 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that monomer B is changed to achieve a change in unit B. Specifically: Example 7: Replacing N,N-dimethylacrylamide with methylenebisacrylamide; Example 8: Using trifluoroethyl acrylate instead of N,N-dimethylacrylamide.
[0088] Example 9 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that monomers A and B are changed to simultaneously change unit A and unit B, methyl vinyl sulfone is used instead of methylpropenyl sulfone, and methylenebisacrylamide is used instead of N,N-dimethylacrylamide.
[0089] Examples 10-12 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and secondary battery differs from that of Example 1 in that the amount of monomer A and monomer B added is changed to change the mass percentage of unit A in the polymer. Specifically: Example 10: In step (1), monomer A (methacrylonitrile, 0.2013 g, 0.0030 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 0.6939 g, 0.0070 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0164 g, 0.0001 mol) were added to 100 g of electrolyte, and the rest of the operation was the same as in Example 1.
[0090] Example 11: In step (1), monomer A (methacrylonitrile, 0.0671 g, 0.0010 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 0.8922 g, 0.0090 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0164 g, 0.0001 mol) were added to 100 g of electrolyte, and the rest of the operation was the same as in Example 1.
[0091] Example 12: In step (1), monomer A (methacrylonitrile, 0.2684 g, 0.0040 mol) for forming unit A, monomer B (N,N-dimethylacrylamide, 0.5948 g, 0.0060 mol) for forming unit B, and initiator (azobisisobutyronitrile, 0.0164 g, 0.0001 mol) were added to 100 g of electrolyte, and the rest of the operation was the same as in Example 1.
[0092] Examples 13-14 This application provides a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that the types of organic solvent and / or lithium salt are changed. Example 13: The organic solvent is a mixture of EC, EMC and DMC in a volume ratio of 1:1:1, and the lithium salt is LiPF6 and LiTFSI, wherein the molar concentration of LiPF6 is 1 mol / L and the molar concentration of LiTFSI is 0.2 mol / L. Example 14: The organic solvent is a mixture of EC, EMC and EA in a volume ratio of 3:6:1.
[0093] Comparative Example 1 This application provides a comparative example of a gel polymer electrolyte and a secondary battery. The difference between the preparation method of the gel polymer electrolyte and the secondary battery in Example 1 is that it is not a gel polymer electrolyte, that is, it only has an electrolyte and no polymer.
[0094] Comparative Example 2 This application provides a comparative example of a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that there is no monomer A, that is, no unit A in the structure.
[0095] Comparative Example 3 This application provides a comparative example of a gel polymer electrolyte and a secondary battery. The preparation method of the gel polymer electrolyte and the secondary battery differs from that of Example 1 in that there is no monomer B, that is, no unit B in the structure.
[0096] The types of unit A, unit B, mass percentage W of polymer in gel polymer electrolyte, molar percentage M of unit A in polymer, type of organic solvent, and type of lithium salt in the examples and comparative examples are shown in Table 1. Among them, the structural formula of unit A corresponding to methacrylonitrile in monomer A is shown in formula c1, the structural formula of unit A corresponding to methyl vinyl sulfone is shown in formula a1, and the structural formula of 4-vinylbenzyl nitrile is shown in formula c2. The structural formula of unit B corresponding to N,N-dimethylacrylamide in monomer B is shown in formula f1, the structural formula of unit B corresponding to methylenebisacrylamide is shown in formula e1, and the structural formula of unit B corresponding to trifluoroethyl acrylate is shown in formula h1. Formula c1 Formula a1 Formula c2; Formula f1 Formula e1 Formula h1.
[0097] Table 1 The performance tests of the secondary batteries prepared in the examples and comparative examples include the following aspects: (1) Cyclic performance testing: ① Charge the secondary battery at 0.5C to 4.35V at 25℃, with a cutoff current of 0.02C, and let it rest for 5 minutes; ② The secondary battery is discharged at 0.2C to 2.8V. The discharge capacity and thickness of the battery at this point are denoted as D. 前 H 前 ; ③ Charge the secondary battery at 3C to 4.35V, with a cutoff current of 0.02C, and let it rest for 5 minutes; ④ Discharge the secondary battery at 0.7C to 2.8V, let it stand for 5 minutes; ⑤ Repeat steps ③ and ④ above 1000 times, then measure the discharge capacity and thickness of the secondary battery at this point, and record it as D. 后 H 后 Wherein, capacity retention rate = D 后 / D 前 ×100%. Expansion rate = H 后 / H 前 ×100%.
[0098] (2) Ratio testing performance test: ① Charge the secondary battery at a constant current of 0.5C to 4.25V at 25℃, then charge it at a constant voltage to the cutoff current of 0.02C, and let it rest for 5 minutes; ② Discharge the secondary battery at a constant current of 0.2C to 2.8V, and record the discharge capacity at this point, denoted as D. 0.2 Let it sit for 5 minutes; ③ Repeat step ① to charge; ④ Discharge the secondary battery at a constant current of 0.5C to 2.8V, record the discharge capacity, and denot it as D. 0.5 Let it sit for 5 minutes; ⑤ Repeat step ① to charge; ⑥ Discharge the secondary battery at a constant current of 1C to 2.8V, record the discharge capacity, and let it rest for 5 minutes; ⑦ Repeat step ① to charge; ⑧ Discharge the secondary battery at a constant current of 2C to 2.8V, record the discharge capacity, and let it rest for 5 minutes; 9. Repeat step ① to charge; ⑩ Discharge the secondary battery at a constant current of 3C to 2.8V, record the discharge capacity as D3, and let it rest for 5 minutes; Corresponding calculation of magnification performance: 0.5C ratio retention rate (%) = D 0.5 / D 0.2 ×100%; 3C ratio retention rate (%) = D3 / D 0.2 ×100%.
[0099] The results are shown in Table 2. Table 2 As can be seen from Table 2, when the technical solution provided in this application is adopted, the obtained secondary battery has good cycle performance and rate performance; specifically, the capacity retention rate of the obtained secondary battery is above 88.43%, the thickness expansion rate is below 9.95%, and the 3C discharge capacity ratio is above 66.51%. As can be seen from Examples 1-14 and Comparative Example 1, compared with electrolytes without polymers, this application can significantly improve the cycle performance and rate performance of secondary batteries; as can be seen from Examples 1-14 and Comparative Examples 2-3, the effect of this application cannot be achieved when either unit A or unit B of the structure of this application is missing.
[0100] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of this application and not to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A gel polymer electrolyte, comprising a polymer and an electrolyte solution, characterized in that, The polymer comprises unit A and unit B; Unit A includes at least one of sulfone and cyano groups; Unit B includes at least one of amide group and fluoroalkyl group.
2. The gel polymer electrolyte according to claim 1, characterized in that, The polymer in the gel polymer electrolyte has a mass percentage greater than 0% and less than or equal to 3%.
3. The gel polymer electrolyte according to claim 1, characterized in that, The unit A includes at least one of the structures shown in equations a-d: Formula a Formula b Formula c Formula d; Among them, R1 is selected from C1-C 20 Alkyl, C1-C 20 Oxyalkylene, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R2 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R10 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R11 and R12 are selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups.
4. The gel polymer electrolyte according to claim 1, characterized in that, The unit B includes at least one of the structures shown in equations e-h: Formula e Formula f Formula g, Formula h; Among them, R3 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R4 and R5 are each independently selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R6 is selected from C1-C 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any one of the fluoroaromatic groups; R7 and R8 are each independently selected from hydrogen, C1-C. 20 Alkyl, C1-C 20 Fluoroalkyl, C6-C 20 Aromatic group, C6-C 20 Any of the fluoroaromatic groups, and at least one of R6, R7, and R8 includes C1-C. 20 Fluorinated alkyl or C6-C 20 Fluorinated aromatic groups; R9 is selected from C1-C 20 Fluoroalkyl, C6-C 20 Any one of the fluoroaromatic groups.
5. The gel polymer electrolyte according to claim 3, characterized in that, The unit A has the structure shown in formula a, and R1 is selected from ethyl; And / or, the unit A has the structure shown in formula c, and R10 is selected from ethyl.
6. The gel polymer electrolyte according to claim 4, characterized in that, The unit B has the structure shown in formula e, and R3 is selected from methylene; And / or, the unit B has the structure shown in formula h, and R9 is trifluoromethyl.
7. The gel polymer electrolyte according to claim 1, characterized in that, In the polymer, the molar percentage of unit A is 10-40%.
8. The gel polymer electrolyte according to claim 1, characterized in that, The electrolyte comprises an organic solvent and a lithium salt; The organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, methyl ethyl carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,3-dioxolane, dimethoxyethane, tetraethylene glycol dimethyl ether, ethyl acetate, and ethyl propionate. The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium di(trifluoromethanesulfonyl)imide, lithium bis(oxalato)borate, lithium difluorooxalato)borate, and lithium hexafluoroarsenate.
9. A secondary battery, characterized in that, The gel polymer electrolyte as described in any one of claims 1-8.
10. An electrical device, characterized in that, The electrical device includes the secondary battery as described in claim 9.